The Dimensional Analysis of School Based Pesantren Design Development - Muhammad Anggung Manumanoso Prasetyo; Khairul Anwar; Nova Asvio; Zaharuddin M (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2022)
The development dimension refers to managerial concept of education strategies. Analysis on the implementation of strategic management at school was conducted using SWOT analysis. This research aims to determine the education strategic management model applied at School Based Pesantren in Aceh Province. This research used qualitative approach with survey method and analytic study. The results show that the organizational development begins with the high ideals of teachers abilitty that supported by institutional independence in school management. The finding revealed that the effectiveness of school development refers to the instilling of the values ​​of pesantren, namely the spirit of sincerity; hence the teachers did not depend on school for their lives. As for the stabilization of the ubudiyyah of the students, it helps in increasing academic achievement. Keywords: Dimensional Analysis, Islamic Based-School, Design Development Pesantren